Support For Muslim Friendly Tourist Destinations in Makassar by Designing Ergonomics Based Ablution Places Using Approach of an Anthropometric - Nusran, Muhammad; Rahmadhani, Muhammad Nur; Padhil, Ahmad; Afiah, Irma Nur; Marasabessy, Sitnah Aisyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The ablution place is one of the places that is always used as an initial means of prayer. From the results of the discussion, it is known that there are several design sizes that have been changed such as the height of the faucet from 100 cm to 136 cm, the width of the gutter from 20 cm to 25 cm and the addition of a shelf with a height of 120 cm to 163 cm to be used to put songkok and other items. Soap height from 110 cm to 140 cm. In addition, the addition of anti-slip rubber carpet on the floor along the ablution place is needed to provide safety so as not to slip due to slippery floors and the addition of a 35 cm high footrest from the 95 % PL percentile to make it easier to wash your feet and be safe and comfortable during ablution.Second, anti-slip floor surfaces to prevent slipping accidents, which often occur in wet areas. Third, the provision of physical supports such as handrails to assist users who need extra help, such as the elderly or those with limited mobility. By designing an ergonomic ablution place, it will enrich the literature in ergonomic design studies and also a commitment to improving the quality of life and spirituality of mosque worshipers, so that Muslim-friendly tourist destination facilities in halal tourism will be more attractive to visit